Analysis of the Effect of Liquidity on Firm Value with Profitability as a Mediating Variable at PT Gudang Garam Tbk 2019 – 2023 - Saputra, Andrian Rizki; Zulkarnaen, Muhamad; Maiyaliza, Maiyaliza (Rescollacom (Research Collaborations Community), 2025)
This study aims to examine the effect of liquidity on firm value with profitability as a mediating variable in PT Gudang Garam Tbk from 2019 to 2023. Using a quantitative approach with path analysis and secondary data from the company’s financial reports, this research tests the relationship among liquidity (measured by Current Ratio), profitability (measured by Return on Assets), and firm value (measured by Price to Book Value). The results indicate that liquidity has no significant effect on profitability, and similarly, liquidity does not significantly affect firm value. However, profitability has a significant positive effect on firm value. Furthermore, profitability is not proven to mediate the effect of liquidity on firm value. The findings suggest that while maintaining optimal liquidity is important, it is profitability that plays a more vital role in enhancing firm value. Management is advised to prioritize strategies that improve profitability to increase shareholder value